Analisis Pengendalian Kualitas Produksi Pakaian Dengan Metode SQC (Analysis of Clothing Production Quality Control Using the SQC Method - Aprilia, Nadia; Aslami, Nuri; Harianto, Budi (STIE Malangkucecwara, 2024)
This study aims to determine the quality control of shirt production in CV. Sumatra Agung Makmur. This study uses case studies using descriptive analysis, and data is collected through observation, interviews, and documentation. The data analyzed from April 2021 to April 2024, the data includes 15,831 production data and 1,362 production defect data. The data was processed using Microsoft Excel and Minitab21 software. The data analysis technique uses Statistical Quality Control (SQC) with 7 tools. The results of the calculations on P, CL, UCL and LCl, show that in the 2nd month the data passed the control limit. Proportion in the 2nd month is 0.121291449, CL is 0.086033731, UCL is 0.11088384, and LCL is 0.061183616. Based on the results of the analysis, it was concluded that there was a need to improve the quality of the shirt production process at CV. Sumatra Agung Makmur.